2015
DOI: 10.1111/head.12655
|View full text |Cite
|
Sign up to set email alerts
|

Glial Attenuation With Ibudilast in the Treatment of Medication Overuse Headache: A Double‐Blind, Randomized, Placebo‐Controlled Pilot Trial of Efficacy and Safety

Abstract: Using the current dosing regimen, ibudilast does not improve headache or reduce opioid use in patients with MOH without mandated opioid withdrawal. However, it would be of interest to determine in future trials if ibudilast is able to improve ease of withdrawal during a forced opioid down-titration when incorporated into an MOH detoxification program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…Our results are in agreement with a recently published finding by our group, which found ibudilast to have no effect in reducing headache index or in reducing opioid intake in medi cation overuse headache patients 41. However, the study also measured toll-like receptor (TLR) reactivity from peripheral blood mononuclear cells and found ibudilast to significantly reduce the proinflammatory cytokine (interleukin 1β) levels from ex vivo stimulation with TLR-2 or TLR-4 agonists.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with a recently published finding by our group, which found ibudilast to have no effect in reducing headache index or in reducing opioid intake in medi cation overuse headache patients 41. However, the study also measured toll-like receptor (TLR) reactivity from peripheral blood mononuclear cells and found ibudilast to significantly reduce the proinflammatory cytokine (interleukin 1β) levels from ex vivo stimulation with TLR-2 or TLR-4 agonists.…”
Section: Discussionsupporting
confidence: 92%
“…For example, minocycline treatment results in pain attenuation in the clinic [ 150 ], but PPF shows no pain attenuation in human trials [ 147 ]. Administration of ibudilast has been shown to attenuate peripheral nerve injury-induced and paclitaxel-induced pain in an animal study [ 151 ]; however, this effect is not observed in a clinical trial [ 152 ]. Although most animal studies have demonstrated that glial modulation is efficacious in treating neuropathic pain [ 153 ], future studies in humans must (1) characterize the effects of glial modulation on glial activation and pain severity and (2) optimize the administration route and application time in order to identify the most promising translational applications of glial modulation in human neuropathic pain [ 154 ].…”
Section: Clinical Applications and Limitations Of Glial Activationmentioning
confidence: 99%
“…Of interest for the treatment of opioid withdrawal, another study in a rat model of diarrhea-predominant irritable bowel syndrome found that pioglitazone significantly reduced defecation frequency, produced a shift from watery stool to hard stool, and increased nociceptive thresholds [30]. On the other hand, clinical trials in humans failed to demonstrate sufficient efficacy of pioglitazone on the oxycodone abuse liability of nondependent opioid users [31] and in the treatment of opioid use withdrawal. Together with the observations made with SJP-005, this encourages further research into the antinociceptive properties and potential opioid sparing properties of PPAR-γ agonists.…”
Section: Discussionmentioning
confidence: 99%